Gel electrolyte composition, secondary battery, battery module, battery pack, and electric device

CN119213597APending Publication Date: 2024-12-27CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280096224.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The liquid electrolyte in existing secondary batteries is prone to side reactions with the metal negative electrode, leading to performance degradation and safety hazards. In addition, dendrites may be generated during the cycle, leading to short circuits and explosion accidents, which cannot meet the application needs of the new generation of electrochemical systems.

Method used

Develop a gel electrolyte composition with a suitable viscosity range that takes into account the fluidity of liquid electrolytes and the safety and reliability of all-solid electrolytes, and improves ionic conductivity and interfacial dynamics by controlling the content of solvents, electrolyte salts, and polymers performance, reduce gas production at high temperatures, and enhance battery safety.

Benefits of technology

It improves the comprehensive performance of the battery, including improving the ion conductivity, Coulombic efficiency and cycle performance at room temperature and high temperature, broadening the temperature range of the battery, reducing battery safety risks, and avoiding dendrite formation and explosion accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213597A_ABST
    Figure CN119213597A_ABST
Patent Text Reader

Abstract

The invention provides a gel electrolyte composition, a secondary battery, a battery module, a battery pack and an electric device. The viscosity of the gel electrolyte composition at 25 DEG C is from 500 mPa * s to 100,000 mPa * s. The gel electrolyte composition has a proper viscosity range, on one hand, the interface wettability of the battery can be increased, the ionic conductivity of the gel electrolyte composition at room temperature and high temperature can be improved, and on the other hand, the interface side reaction of the gel electrolyte composition can be weakened, and the coulombic efficiency of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Gel electrolyte composition, secondary battery, battery module, battery pack and electrical device Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a gel electrolyte composition, a secondary battery, a battery module, a battery pack, and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage systems such as hydropower, thermal, wind, and solar power plants, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace, and other fields. With the widespread use of secondary batteries, higher requirements have been placed on their performance and safety.

[0003] At present, most batteries use liquid electrolytes. However, on the one hand, liquid electrolytes are prone to side reactions with metal negative electrodes, resulting in decreased battery performance and increased safety hazards. On the other hand, liquid electrolytes are prone to generate dendrites at the negative electrode during the cycle process, causing battery short circuits. In severe cases, it can cause battery explosion accidents, which cannot meet the application needs of the new generation of electrochemical systems.

[0004] Summary of the Invention

[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a gel electrolyte composition that takes into account the fluidity of a liquid electrolyte and the safety and reliability of an all-solid-state electrolyte, thereby improving the battery's safety performance while also taking into account the battery's dynamic performance and thus improving the battery's overall performance.

[0006] In a first aspect of the present application, a gel electrolyte composition is provided, wherein the viscosity of the gel electrolyte composition at 25° C. is 500 mPa·s to 100,000 mPa·s.

[0007] The gel electrolyte composition has an appropriate viscosity range, which not only provides ion transport channels and improves ionic conductivity, but also offers high safety performance, reducing battery gassing, especially at high temperatures, and improving battery safety. This effectively leverages the advantages of both liquid and all-solid electrolytes. The gel electrolyte composition has an appropriate viscosity range, which not only increases the interfacial wettability of the battery, facilitating the improvement of the interfacial dynamics of the gel electrolyte composition at room temperature and high temperatures, but also reduces interfacial side reactions of the gel electrolyte composition, particularly contributing to improved coulombic efficiency of the battery at high temperatures.

[0008] In any embodiment, the gel electrolyte composition comprises a solvent, wherein, based on the total amount of the solvent, the amount of the free solvent in the gel electrolyte composition accounts for n FS0% <n FS ≤70%.

[0009] Controlling the ratio of the amount of free solvent in the gel electrolyte composition to the total amount of solvent can ensure that the gel electrolyte composition has high ionic conductivity, excellent interfacial kinetics and mass transfer processes, which is beneficial to improving the ionic conductivity of the gel electrolyte composition at room temperature and high temperature. At the same time, it can also avoid the increase in gas production caused by the excessively high ratio of free solvent, resulting in an increase in the battery expansion rate and reduced battery safety.

[0010] In any embodiment, the mass content of the solvent is 20% to 75% based on the total mass of the gel electrolyte composition.

[0011] Based on the total mass of the gel electrolyte composition, controlling the mass content of the solvent to 20% to 75% is beneficial to improving the ionic conductivity of the gel electrolyte composition at room temperature and high temperature, improving the coulombic efficiency of the battery at room temperature and high temperature, and the cycle performance at room temperature, thereby broadening the temperature operating range of the battery.

[0012] In any embodiment, the gel electrolyte composition further includes an electrolyte salt, and the mass content of the electrolyte salt is 5% to 70% based on the total mass of the gel electrolyte composition.

[0013] Based on the total mass of the gel electrolyte composition, controlling the mass content of the electrolyte salt to 5% to 70% is beneficial to improving the ionic conductivity of the gel electrolyte composition at room temperature and high temperature, improving the coulombic efficiency of the battery at room temperature and high temperature, and the cycle performance at room temperature, thereby broadening the temperature operating range of the battery.

[0014] In any embodiment, the gel electrolyte composition further comprises a polymer, and the mass content of the polymer is 2% to 20% based on the total mass of the gel electrolyte composition.

[0015] Based on the total mass of the gel electrolyte composition, controlling the mass content of the polymer to 2% to 20% is beneficial to improving the ionic conductivity of the gel electrolyte composition at room temperature and high temperature, improving the coulombic efficiency of the battery at room temperature and high temperature, and the cycle performance at room temperature, thereby broadening the temperature operating range of the battery.

[0016] In any embodiment, the gel electrolyte composition is a supersaturated gel electrolyte composition at 25°C.

[0017] In any embodiment, the supersaturated gel electrolyte composition has a viscosity of 3000 mPa·s to 100000 mPa·s at 25° C., and a viscosity of 500 mPa·s to 5000 mPa·s at 60° C.

[0018] In any embodiment, the supersaturated gel electrolyte composition has a viscosity of 3000 mPa·s to 11000 mPa·s at 25° C., and a viscosity of 500 mPa·s to 3000 mPa·s at 60° C.

[0019] The supersaturated gel electrolyte composition has a suitable viscosity range, which is beneficial to improving the ionic conductivity of the gel electrolyte composition at room temperature and high temperature, and improving the coulombic efficiency of the battery at 60° C., thereby widening the temperature operating range of the battery.

[0020] In any embodiment, the supersaturated gel electrolyte composition includes dissolved electrolyte salt and precipitated crystals of electrolyte salt.

[0021] The precipitated crystallized electrolyte salt is uniformly dispersed in the supersaturated gel electrolyte composition system, further enhancing the mechanical properties of the supersaturated gel electrolyte composition.

[0022] In any embodiment, the median particle size of the precipitated crystallized electrolyte salt is 100 μm or less.

[0023] The median particle size of the precipitated crystallized electrolyte salt is controlled to be less than or equal to 100 μm to prevent the particles from being too large and hindering the transmission of ions.

[0024] In any embodiment, based on the total mass of the supersaturated gel electrolyte composition, the mass content of the electrolyte salt is 30% to 70%, the mass content of the solvent is 20% to 60%, and the mass content of the polymer is 2% to 20%.

[0025] Based on the total mass of the supersaturated gel electrolyte composition, the mass content of the electrolyte salt is controlled to be 30% to 70%, the mass content of the solvent is controlled to be 20% to 60%, and the mass content of the polymer is controlled to be 2% to 20%. This is beneficial to improving the ionic conductivity of the supersaturated gel electrolyte composition at room temperature and high temperature, and improving the coulombic efficiency of its battery at 60°C.

[0026] In any embodiment, the electrolyte salt comprises a sodium salt, and the sodium salt comprises one or more of sodium chloride, sodium bromide, sodium nitrate, sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium tetrafluoroyttrium, sodium hexafluoroarsenate, sodium tetraphenylborate, sodium acetate, sodium trifluoroacetate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, and sodium (perfluorobutylsulfonyl)imide, and optionally comprises one or more of sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide.

[0027] The above sodium salts are all beneficial for improving the coulombic efficiency of the battery at 60°C and 80°C, thereby improving the battery performance. Sodium salts include one or more of sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, which can further improve the coulombic efficiency of the battery at 60°C and the cycle performance of the battery at 25°C and 60°C, significantly improving the battery performance.

[0028] In any embodiment, the solvent comprises one or more of an ether organic solvent, an ester organic solvent, and a sulfur-containing organic solvent, and comprises one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, γ-butyrolactone, 1,3-propane sultone, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, propyl propionate, ethyl butyrate, and dimethyl sulfoxide, and optionally comprises one or more of ethylene glycol dimethyl ether, tetrahydrofuran, and 1,3-dioxolane.

[0029] The above solvents are all beneficial for improving the coulombic efficiency of the battery at 60°C. The solvent is selected from one or more of ethylene glycol dimethyl ether, tetrahydrofuran, and 1,3-dioxolane, which can further improve the coulombic efficiency of the battery at room temperature and high temperature, improve the cycle performance of the battery at 25°C and 60°C, and reduce the thickness expansion rate of the battery at 25°C and 60°C, thereby significantly improving the performance and safety of the battery.

[0030] In any embodiment, the polymer comprises one or more of polyethylene oxide, polyethylene glycol, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinylidene fluoride, polyvinyl alcohol, polyacrylonitrile, polyvinyl chloride, polyacrylamide, polytrimethylene carbonate, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer, and optionally comprises one or more of polyethylene oxide, polyethylene glycol, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer.

[0031] The aforementioned polymers are beneficial for improving the coulombic efficiency of the battery at 25°C and 60°C, as well as the number of cycles during which the battery retains 80% of its capacity at 60°C. The polymers, selected from one or more of polyethylene oxide, polyethylene glycol, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymers, can further reduce the thickness expansion rate of the battery at 25°C, lower gas production, and significantly improve battery safety.

[0032] In any embodiment, the electrolyte salt includes one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the solvent includes one or more of ethylene glycol dimethyl ether, tetrahydrofuran, and 1,3-dioxolane; and the polymer includes one or more of polyethylene oxide, polyethylene glycol, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer.

[0033] The gel electrolyte composition can have both the electrical performance and safety of a battery.

[0034] A second aspect of the present application provides a secondary battery comprising a positive electrode sheet and the gel electrolyte composition described in any embodiment.

[0035] The secondary battery has excellent cycle performance.

[0036] In any embodiment, the secondary battery includes at least one of a lithium battery and a sodium battery.

[0037] In any embodiment, the secondary battery is a negative electrode-free sodium battery. The negative electrode-free sodium battery can have a high energy density.

[0038] In any embodiment, the CB value of the negative electrode-free sodium battery is less than or equal to 0.1.

[0039] In any embodiment, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes at least one of a transition metal layered oxide, a polyanion compound, and a Prussian blue compound, including NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2、Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9 Mg 1 / 18 O2, Na4Fe3(PO4)2P2O7, NaFePO4, Na3V2(PO4)3, Na 1.9 One or more of CoFe(CN)6, Na2NiFe(CN)6, and NaMnFe(CN)6.

[0040] The above-mentioned positive electrode active materials can all give the battery excellent electrical properties.

[0041] In any embodiment, the surface of the positive electrode active material has a coating layer, and the coating layer includes one or more of carbon material, ZrO2, TiO2, polyaniline, polypyrrole, poly (3,4-ethylenedioxythiophene), aluminum oxide, zinc oxide, titanium oxide, zirconium oxide, magnesium oxide, silicon oxide, lanthanum oxide, sodium fluoride, lithium fluoride and aluminum fluoride, and the carbon material includes one or more of amorphous carbon, graphite, and graphene.

[0042] The surface of the positive electrode active material has a coating layer, which is more conducive to improving the coulombic efficiency of the battery at room temperature and high temperature, improving the cycle performance of the battery at 25°C, and reducing the thickness expansion rate of the battery at 25°C and 60°C, reducing gas production, and greatly improving the performance and safety of the battery.

[0043] A third aspect of the present application provides a battery module, comprising the secondary battery according to the second aspect of the present application.

[0044] A fourth aspect of the present application provides a battery pack, comprising the secondary battery of the second aspect of the present application or the battery module of the third aspect of the present application.

[0045] A fifth aspect of the present application provides an electrical device comprising at least one of the secondary battery of the second aspect of the present application, the battery module of the third aspect of the present application, and the battery pack of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0047] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;

[0048] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0049] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0050] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;

[0051] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.

[0052] Description of reference numerals:

[0053] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0054] Below, embodiments of the gel electrolyte composition, secondary battery, battery module, battery pack, and electrical device of the present application are described in detail, with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid unnecessary length in the following description and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0055] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0056] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0057] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0058] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0059] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0060] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0061] Currently, liquid electrolytes have many problems, and all-solid-state electrolytes have attracted the attention of researchers because they can effectively suppress side reactions at the metal anode interface and the safety issues caused by the corresponding dendrites. However, most all-solid-state electrolytes have difficulty forming excellent interfacial contact with the electrode, which affects the electrolyte's ionic conductivity and interfacial dynamics, and reduces the battery's rate performance. Therefore, it is necessary to develop a new electrolyte system that takes into account both the electrochemical performance and safety of the battery.

[0062] [Gel Electrolyte Composition]

[0063] Based on this, the present application proposes a gel electrolyte composition, wherein the viscosity of the gel electrolyte composition at 25° C. is 500 mPa·s to 100,000 mPa·s.

[0064] In this article, the gel electrolyte composition refers to an electrolyte composition that has both the fluidity of a liquid electrolyte and the mechanical strength of an all-solid electrolyte.

[0065] In some embodiments, the viscosity of the gel electrolyte composition at 25° C. may be 500 mPa·s, 1000 mPa·s, 2000 mPa·s, 3000 mPa·s, 4000 mPa·s, 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, 8000 mPa·s, 9000 mPa·s, 10000 mPa·s, 20000 mPa·s, 30000 mPa·s, 40000 mPa·s, 50000 mPa·s, 60000 mPa·s, 70000 mPa·s, 80000 mPa·s, 90000 mPa·s or 100000 mPa·s.

[0066] In this context, the viscosity of the gel electrolyte composition can be tested using methods known in the art, such as measuring the viscosity of the slurry using a rotary viscometer. A suitable viscometer rotor is selected and secured. The slurry is placed below the viscometer rotor, just enough to cover the rotor scale. The instrument model is: Shanghai Fangrui NDJ-5S, rotors: 63# (2000-10000 mPa.s), 64# (10000-50000 mPa.s), rotation speed: 12 rpm, and the test duration is 5 minutes. The reading is then read after the display stabilizes.

[0067] The gel electrolyte composition has an appropriate viscosity range, which not only provides ion transport channels and improves its ionic conductivity, but also offers high safety. This prevents the solvent in the electrolyte composition from generating large amounts of gas, improving battery safety and leveraging the advantages of both liquid and all-solid electrolytes. The gel electrolyte composition has an appropriate viscosity range, which not only increases the interfacial wettability of the battery, but also helps improve the interfacial dynamics of the gel electrolyte composition at room temperature and high temperatures. It also reduces interfacial side reactions in the gel electrolyte composition, particularly contributing to improved coulombic efficiency at high temperatures.

[0068] Herein, the term "room temperature" refers to 5°C to 35°C.

[0069] Herein, the term "high temperature" refers to 40°C to 80°C.

[0070] In this article, coulombic efficiency refers to the average coulombic efficiency, which is mainly used to characterize the average value of the ratio of battery discharge capacity to charge capacity during the cycle process. It can reflect the degree of metal ion consumption and can be tested by any known method.

[0071] Herein, ionic conductivity is mainly used to characterize the ion transport capability of the gel electrolyte composition, and can reflect the ion transport capability of the gel electrolyte composition, and can be tested by any known method.

[0072] In some embodiments, the gel electrolyte composition comprises a solvent, wherein the amount of free solvent in the gel electrolyte composition accounts for n of the total amount of solvent. FS 0% <n FS In some embodiments, based on the total mass of the solvent, the mass content of the free solvent in the gel electrolyte composition accounts for n% of the total mass of the solvent. FS The options are 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%.

[0073] In this article, the test of the proportion of the amount of free solvent in the gel electrolyte composition to the total amount of solvent can be carried out by methods known in the art, such as using a Nicolet iS5 Fourier transform infrared spectrometer to test the infrared spectrum of the gel electrolyte composition, normalizing the spectrum, and recording the intensity of the solvent characteristic peak as I1. The solvent of the gel electrolyte composition is used as a reference sample to measure its infrared spectrum, normalizing the spectrum, and recording the intensity of the corresponding characteristic peak of the solvent as I2. I1 / I2 is used as the ratio of the amount of free solvent in the gel electrolyte composition to the total amount of solvent. Among them, the solvent characteristic peak is selected according to the type of solvent. For ether solvents, the characteristic peak of CO is located at 800-900 cm -1 For ester solvents, the characteristic peak of C=O is located between 850 and 950 cm -1 Between 1700~1800cm -1 In this article, the term "solvent" refers to any liquid that can dissolve solid, liquid or gaseous solutes. Solvents include free solvents and non-free solvents.

[0074] In this article, the term "free solvent" refers to solvent molecules that are free to move without any coordination with anions or cations, and without any hydrogen bonding or hydrogen-bonding-like interactions between solvent molecules. For example, a free solvent does not participate in the solvation structure of the electrolyte salt, does not coordinate with anions or cations of the electrolyte salt, does not participate in the swelling of the polymer, and does not form strong binding interactions with other functional groups.

[0075] As used herein, the term "non-free solvent" refers to solvent molecules that coordinate with anions and cations, or form hydrogen bonds or hydrogen-bond-like interactions between solvent molecules, preventing them from moving freely. Controlling the ratio of the free solvent content to the total solvent content in a gel electrolyte composition ensures that the gel electrolyte composition exhibits high ionic conductivity, excellent interfacial dynamics, and mass transfer processes, thereby improving the ionic conductivity of the gel electrolyte composition at both room and high temperatures. It also prevents excessively high free solvent content from increasing gas production, which can lead to increased battery expansion and reduced safety.

[0076] In some embodiments, the mass content of the solvent is 20% to 75% based on the total mass of the gel electrolyte composition. In some embodiments, the mass content of the solvent is 20%, 22%, 25%, 30%, 35%, 38%, 40%, 45%, 47%, 50%, 53%, 55%, 60%, 62%, 65%, 70% or 75% based on the total mass of the gel electrolyte composition.

[0077] Based on the total mass of the gel electrolyte composition, controlling the mass content of the solvent to 20% to 75% is beneficial to improving the ionic conductivity of the gel electrolyte composition at room temperature and high temperature, improving the coulombic efficiency of the battery at room temperature and high temperature, and the cycle performance at room temperature, thereby broadening the temperature operating range of the battery.

[0078] In some embodiments, the gel electrolyte composition further comprises an electrolyte salt, and the mass content of the electrolyte salt is 5% to 70% based on the total mass of the gel electrolyte composition. In some embodiments, the mass content of the electrolyte salt can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70% based on the total mass of the gel electrolyte composition.

[0079] Based on the total mass of the gel electrolyte composition, controlling the mass content of the electrolyte salt to 5% to 70% is beneficial to improving the ionic conductivity of the gel electrolyte composition at room temperature and high temperature, improving the coulombic efficiency of the battery at room temperature and high temperature, and the cycle performance at room temperature, thereby broadening the temperature operating range of the battery.

[0080] In some embodiments, the gel electrolyte composition further comprises a polymer, and the mass content of the polymer is 2% to 20% based on the total mass of the gel electrolyte composition. In some embodiments, the mass content of the polymer can be 2%, 4%, 5%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, or 20% based on the total mass of the gel electrolyte composition.

[0081] Based on the total mass of the gel electrolyte composition, controlling the mass content of the polymer to 2% to 20% is beneficial to improving the ionic conductivity of the gel electrolyte composition at room temperature and high temperature, improving the coulombic efficiency of the battery at room temperature and high temperature, and the cycle performance at room temperature, thereby broadening the temperature operating range of the battery.

[0082] In some embodiments, the gel electrolyte composition is a supersaturated gel electrolyte composition at 25°C.

[0083] The supersaturated gel electrolyte composition refers to a gel electrolyte composition in which a portion of the electrolyte salt is precipitated at room temperature (5° C. to 30° C.) because the electrolyte salt dissolved in the gel electrolyte composition exceeds the saturation concentration.

[0084] Compared with other gel electrolyte compositions, the supersaturated gel electrolyte composition has a higher electrolyte salt concentration. As the temperature increases, the electrolyte salt particles precipitated in the supersaturated gel electrolyte composition will further dissolve, forming a more stable battery system. Moreover, the supersaturated state of the supersaturated gel electrolyte composition can cause the solvation structure morphology of the electrolyte salt to change, which also helps to improve the chemical stability of the battery at high temperatures. In summary, the supersaturated gel electrolyte composition can improve the coulombic efficiency and cycle performance of the battery at high temperatures, reduce the gas production of the battery at high temperatures, and simultaneously improve the electrochemical performance and safety performance of the battery at high temperatures.

[0085] In some embodiments, the supersaturated gel electrolyte composition has a viscosity of 3000 mPa·s to 100000 mPa·s at 25° C., and a viscosity of 500 mPa·s to 5000 mPa·s at 60° C.

[0086] In some embodiments, the supersaturated gel electrolyte composition has a viscosity of 3000 mPa·s to 11000 mPa·s at 25° C., and a viscosity of 500 mPa·s to 3000 mPa·s at 60° C.

[0087] In some embodiments, the viscosity of the supersaturated gel electrolyte composition at 25° C. may be 3000 mPa·s, 4000 mPa·s, 5000 mPa·s, 6000 mPa·s, 7000 mPa·s, 8000 mPa·s, 9000 mPa·s, 10000 mPa·s, 20000 mPa·s, 30000 mPa·s, 40000 mPa·s, 50000 mPa·s, 60000 mPa·s, ·s, 70000 mPa·s, 80000 mPa·s, 90000 mPa·s or 100000 mPa·s, and the viscosity of the supersaturated gel electrolyte composition at 60° C. may be 500 mPa·s, 600 mPa·s, 700 mPa·s, 800 mPa·s, 900 mPa·s, 1000 mPa·s, 1500 mPa·s, 2000 mPa·s, 2500 mPa·s or 3000 mPa·s.

[0088] The supersaturated gel electrolyte composition has a suitable viscosity range, which is beneficial to improving the ionic conductivity of the supersaturated gel electrolyte composition at room temperature and high temperature, and improving the coulombic efficiency of the battery at 60° C., thereby widening the temperature operating range of the battery.

[0089] In some embodiments, the supersaturated gel electrolyte composition includes dissolved electrolyte salt and precipitated crystals of electrolyte salt.

[0090] Herein, "the electrolyte salt crystallizes out" means that the concentration of the electrolyte salt exceeds the saturation concentration and a part of the electrolyte salt is precipitated in the form of solid crystals.

[0091] The precipitated crystallized electrolyte salt is uniformly diffused as a dispersed phase in the continuous phase of the supersaturated gel electrolyte composition, further enhancing the mechanical properties of the supersaturated gel electrolyte composition.

[0092] In some embodiments, the median particle size of the crystallized electrolyte salt is less than or equal to 100 μm. In some embodiments, the median particle size of the crystallized electrolyte salt can be 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm or 100 μm.

[0093] In this article, the median particle size of the crystallized electrolyte salt can be measured using methods known in the art. For example, the centrifugal sedimentation method and laser particle size analyzer are used for testing. First, the sample is centrifuged, sedimented, and filtered to obtain the crystallized electrolyte salt. Then, 0.1g to 0.13g of the crystallized electrolyte salt sample to be tested is weighed into a 50mL beaker, 5g of acetone is added, and a stirring bar of approximately 2.5mm is placed in the beaker, which is then sealed with plastic wrap. After ultrasonic treatment for 5 minutes, the sample is transferred to a magnetic stirrer and stirred at 500 rpm for more than 20 minutes. Two samples are taken from each batch for testing. Testing is performed using a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK.

[0094] The median particle size of the crystallized electrolyte salt is controlled to be less than or equal to 100 μm to prevent the crystallized electrolyte salt from settling and to uniformly disperse it in the supersaturated gel electrolyte composition. This can also enhance the mechanical properties of the supersaturated gel electrolyte composition and prevent the particles from being too large and hindering the transmission of ions.

[0095] In some embodiments, based on the total mass of the supersaturated gel electrolyte composition, the mass content of the electrolyte salt is 30% to 70%, the mass content of the solvent is 20% to 60%, and the mass content of the polymer is 2% to 20%. In some embodiments, based on the total mass of the supersaturated gel electrolyte composition, the mass content of the electrolyte salt may be 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% or 70%, the mass content of the solvent may be 20%, 22%, 25%, 27%, 30%, 32%, 35%, 38%, 40%, 45%, 47%, 50%, 53%, 55%, 57% or 60%, and the mass content of the polymer may be 2%, 4%, 5%, 8%, 10%, 12%, 14%, 15%, 16%, 18% or 20%.

[0096] Based on the total mass of the supersaturated gel electrolyte composition, the mass content of the electrolyte salt is controlled to be 30% to 70%, the mass content of the solvent is controlled to be 20% to 60%, and the mass content of the polymer is controlled to be 2% to 20%. This is beneficial to improving the ionic conductivity of the supersaturated gel electrolyte composition at room temperature and high temperature, and improving the coulombic efficiency of its battery at 60°C.

[0097] In some embodiments, the electrolyte salt comprises a sodium salt, and the sodium salt comprises one or more of sodium chloride, sodium bromide, sodium nitrate, sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium tetrafluoroyttrium, sodium hexafluoroarsenate, sodium tetraphenylborate, sodium acetate, sodium trifluoroacetate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, and sodium (perfluorobutylsulfonyl)imide, and optionally comprises one or more of sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide.

[0098] In some embodiments, the sodium salt comprises sodium chloride. In some embodiments, the sodium salt comprises sodium bromide. In some embodiments, the sodium salt comprises sodium hexafluorophosphate. In some embodiments, the sodium salt comprises sodium tetrafluoroborate. In some embodiments, the sodium salt comprises sodium trifluoromethanesulfonate. In some embodiments, the sodium salt comprises sodium bis(fluorosulfonyl)imide. In some embodiments, the sodium salt comprises sodium bis(fluorosulfonyl)imide and sodium bis(trifluoromethylsulfonyl)imide. In some embodiments, the sodium salt comprises sodium tetrafluoroborate and sodium bis(fluorosulfonyl)imide.

[0099] The above sodium salts are all beneficial for improving the coulombic efficiency of the battery at 60°C and 80°C, thereby improving the battery performance. Sodium salts include one or more of sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide, which can further improve the coulombic efficiency of the battery at 60°C and the cycle performance of the battery at 25°C and 60°C, significantly improving the battery performance.

[0100] In some embodiments, the solvent comprises one or more of an ether organic solvent, an ester organic solvent, and a sulfur-containing organic solvent, and comprises one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, γ-butyrolactone, 1,3-propane sultone, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, propyl propionate, ethyl butyrate, and dimethyl sulfoxide, and optionally comprises one or more of ethylene glycol dimethyl ether, tetrahydrofuran, and 1,3-dioxolane.

[0101] In some embodiments, the solvent comprises ethylene glycol dimethyl ether. In some embodiments, the solvent comprises diethylene glycol dimethyl ether. In some embodiments, the solvent comprises triethylene glycol dimethyl ether. In some embodiments, the solvent comprises tetraethylene glycol dimethyl ether. In some embodiments, the solvent comprises tetrahydrofuran. In some embodiments, the solvent comprises 1,3-dioxolane. In some embodiments, the solvent comprises ethylene carbonate. In some embodiments, the solvent comprises ethylene glycol dimethyl ether and tetrahydrofuran. In some embodiments, the solvent comprises ethylene glycol dimethyl ether and 1,3-dioxolane.

[0102] The above solvents are all beneficial for improving the coulombic efficiency of the battery at 60°C. The solvent is selected from one or more of ethylene glycol dimethyl ether, tetrahydrofuran, and 1,3-dioxolane, which can further improve the coulombic efficiency of the battery at room temperature and high temperature, improve the cycle performance of the battery at 25°C and 60°C, and reduce the thickness expansion rate of the battery at 25°C and 60°C, reduce gas production, and significantly improve the performance and safety of the battery.

[0103] In this article, the thickness expansion rate is mainly used to characterize the storage performance of the battery and can reflect the gas production and stability of the battery. It can be tested by any known method.

[0104] In some embodiments, the polymer comprises one or more of polyethylene oxide, polyethylene glycol, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinylidene fluoride, polyvinyl alcohol, polyacrylonitrile, polyvinyl chloride, polyacrylamide, polytrimethylene carbonate, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer, and optionally comprises one or more of polyethylene oxide, polyethylene glycol, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer.

[0105] In some embodiments, the polymer comprises polyethylene oxide. In some embodiments, the polymer comprises polyethylene glycol. In some embodiments, the polymer comprises polyvinyl pyrrolidone. In some embodiments, the polymer comprises polymethyl methacrylate. In some embodiments, the polymer comprises polyvinylidene fluoride. In some embodiments, the polymer comprises poly(vinylidene fluoride-co-hexafluoropropylene) copolymer. In some embodiments, the polymer comprises perfluoropolyether. In some embodiments, the polymer comprises perfluoropolyether and polyethylene oxide. In some embodiments, the polymer comprises polyethylene glycol and polyethylene oxide.

[0106] The above polymers are beneficial for improving the coulombic efficiency of the battery at 25°C and 60°C, as well as the cycling performance of the battery at 60°C. The polymer is selected from one or more of polyethylene oxide, polyethylene glycol, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer, which can further reduce the thickness expansion rate of the battery at 25°C, reduce gas production, and significantly improve battery safety.

[0107] In some embodiments, the electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the solvent comprises one or more of ethylene glycol dimethyl ether, tetrahydrofuran, and 1,3-dioxolane; and the polymer comprises one or more of polyethylene oxide, polyethylene glycol, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer.

[0108] In some embodiments, the electrolyte salt comprises sodium trifluoromethanesulfonate, the solvent comprises ethylene glycol dimethyl ether, and the polymer comprises polyethylene oxide. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the solvent comprises ethylene glycol dimethyl ether, and the polymer comprises polyethylene oxide. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the solvent comprises tetrahydrofuran, and the polymer comprises polyethylene oxide. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the solvent comprises ethylene glycol dimethyl ether, and the polymer comprises polyethylene glycol. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the solvent comprises ethylene glycol dimethyl ether, and the polymer comprises perfluoropolyether. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the solvent comprises ethylene glycol dimethyl ether, and the polymer comprises poly(vinylidene fluoride-co-hexafluoropropylene) copolymer. In some embodiments, the electrolyte salt comprises sodium bis(fluorosulfonyl)imide, the solvent comprises ethylene glycol dimethyl ether, and the polymer comprises perfluoropolyether and polyethylene oxide.

[0109] The gel electrolyte composition can have both the electrical performance and safety of a battery.

[0110] [Positive electrode]

[0111] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, which may include at least one of a layered transition metal oxide, a polyanionic compound, and a Prussian blue compound.

[0112] The transition metal in the layered transition metal oxide can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Optionally, the layered transition metal oxide is, for example, NaxMO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, and 0<x≤1.

[0113] Polyanionic compounds can be metal ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The metal ion can be selected from sodium ion, lithium ion, potassium ion, and zinc ion; the transition metal can be selected from at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be selected from at least one of P, S, and Si; n represents (YO4) n- valence.

[0114] Prussian blue compounds can be compounds containing sodium ions, transition metal ions, and cyanide ions (CN-). The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.

[0115] In some embodiments, the positive electrode sheet includes a positive electrode active material, the positive electrode active material includes at least one of a layered transition metal oxide, a polyanion compound, and a Prussian blue compound, including NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2、Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9 Mg 1 / 18 O2, Na4Fe3(PO4)2P2O7, NaFePO4, Na3V2(PO4)3, Na 1.9 One or more of CoFe(CN)6, Na2NiFe(CN)6, and NaMnFe(CN)6.

[0116] The above-mentioned positive electrode active materials can all give the battery excellent electrical properties.

[0117] In some embodiments, the surface of the positive electrode active material has a coating layer, which includes one or more of a carbon material, ZrO2, TiO2, polyaniline, polypyrrole, poly(3,4-ethylenedioxythiophene), aluminum oxide, zinc oxide, titanium oxide, zirconium oxide, magnesium oxide, silicon oxide, lanthanum oxide, sodium fluoride, lithium fluoride and aluminum fluoride, and the carbon material includes one or more of amorphous carbon, graphite and graphene.

[0118] As used herein, the term "amorphous carbon" refers to a carbon material with a low degree of graphitization and crystallization, which is approximately amorphous and has no specific shape or periodic structure. Examples of amorphous carbon include, but are not limited to, carbon black, charcoal, or coke.

[0119] As used herein, the term "graphite" refers to an allotrope of carbon, including natural graphite and artificial graphite.

[0120] As used herein, the term "graphene" refers to a carbon material in which carbon atoms connected by sp2 hybridization are closely packed into a single-layer two-dimensional honeycomb lattice structure. By way of example, graphene includes but is not limited to single-layer graphene or multi-layer graphene.

[0121] As used herein, the term "single-layer graphene" refers to a single-layer sheet structure composed of carbon atoms densely arranged in a periodic hexagonal honeycomb structure. For example, the thickness of a single-layer graphene is only 0.3 nm to 0.4 nm.

[0122] In this article, the term "multilayer graphene" refers to a stack of 2 to 10 single-layer graphene layers with a total thickness of less than 100 nm.

[0123] The surface of the positive electrode active material has a coating layer, which is more conducive to improving the coulombic efficiency of the battery at room temperature and high temperature, improving the cycle performance of the battery at 25°C, and reducing the thickness expansion rate of the battery at 25°C and 60°C, reducing gas production, and greatly improving the performance and safety of the battery.

[0124] The positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The conductive agent may be selected from one or more of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.

[0125] The positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and optional conductive agent to the positive electrode current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA), and carboxymethyl chitosan (CMCS).

[0126] The positive electrode current collector can be a conductive carbon sheet, metal foil, carbon-coated metal foil, porous metal plate, or a composite current collector. The conductive carbon material of the conductive carbon sheet can be selected from one or more of Super P, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers. The metal material of the metal foil, carbon-coated metal foil, and porous metal plate can each be independently selected from at least one of copper, aluminum, nickel, and stainless steel. The composite current collector can be a composite of metal foil and a polymer-based film.

[0127] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0128] [Negative electrode]

[0129] The negative electrode sheet may include only the negative electrode current collector without including the negative electrode active material.

[0130] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil or copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0131] [Isolation film]

[0132] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0133] In some embodiments, the material of the separator can be selected from at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester, and natural fibers. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0134] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0135] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.

[0136] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the secondary battery can be a soft shell, such as a pouch-type soft shell. The soft shell can be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0137] [Secondary battery]

[0138] A secondary battery includes a positive electrode sheet and a gel electrolyte composition in some embodiments.

[0139] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG2 shows a secondary battery 5 having a square structure as an example.

[0140] In some embodiments, the secondary battery further includes a negative electrode sheet and a separator.

[0141] In some embodiments, the secondary battery includes at least one of a lithium battery and a sodium battery.

[0142] In some embodiments, the secondary battery includes at least one of a potassium battery, a magnesium battery, and a zinc battery.

[0143] In some embodiments, the secondary battery is a negative electrode-less sodium battery.

[0144] The negative electrode-free sodium battery does not contain negative electrode active materials, but only contains a negative electrode current collector. During the first charge, sodium ions obtain electrons on the cathode side and metallic sodium is deposited on the surface of the current collector to form a sodium metal phase. During discharge, the metallic sodium can be converted into sodium ions and return to the positive electrode, realizing cyclic charge and discharge. Compared with sodium ion secondary batteries and sodium metal batteries, negative electrode-free sodium batteries can achieve higher energy density because they are not restricted by negative electrode materials. There is not enough sodium metal in the negative electrode-free sodium battery as a negative electrode material to provide enough sodium elements to the battery. Therefore, the application of the gel electrolyte composition in the negative electrode-free sodium battery can more effectively improve the cycle performance and safety performance of the secondary battery at room temperature / high temperature.

[0145] In some embodiments, the CB value of the negative electrode-free sodium battery is less than or equal to 0.1.

[0146] The CB value is the capacity per unit area of ​​the negative electrode in a secondary battery divided by the capacity per unit area of ​​the positive electrode. Since a battery without a negative electrode contains no negative active material, the capacity per unit area of ​​the negative electrode is relatively small, and the CB value of a secondary battery is less than or equal to 0.1.

[0147] In some embodiments, referring to Figure 3, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The gel electrolyte composition is impregnated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0148] [Battery Module]

[0149] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0150] Figure 4 shows an example battery module 4. Referring to Figure 4 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.

[0151] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0152] [Battery Pack]

[0153] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.

[0154] Figures 5 and 6 illustrate an example battery pack 1. Referring to Figures 5 and 6 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0155] [Electrical devices]

[0156] In one embodiment of the present application, an electric device is provided, comprising at least one of a secondary battery according to any embodiment, a battery module according to any embodiment, or a battery pack according to any embodiment.

[0157] The electrical device includes at least one of the secondary battery, battery module, or battery pack provided in this application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0158] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0159] Figure 7 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.

[0160] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.

[0161] Example

[0162] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0163] 1. Preparation method

[0164] Example 1

[0165] 1) Preparation of gel electrolyte composition

[0166] In a dry argon atmosphere, polyethylene oxide (PEO, weight-average molecular weight 600,000), sodium bis(fluorosulfonyl)imide (NaFSI) and solvent ethylene glycol dimethyl ether (DME) were mixed at room temperature in a mass ratio of 1:1:3 and stirred evenly to completely dissolve NaFSI to obtain a gel electrolyte composition.

[0167] 2) Preparation of positive electrode sheet

[0168] Na4Fe3(PO4)2P2O7 (NFPP) material, conductive agent carbon black, polyvinylidene fluoride binder and N-methylpyrrolidone (NMP) are stirred and mixed in a weight ratio of 8:1:1 to obtain a positive electrode slurry with a solid content of 73%. The positive electrode slurry is then evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying, cold pressing and slitting, the positive electrode sheet is obtained.

[0169] 3) Preparation of negative electrode sheet

[0170] Carbon nanotubes and hydroxymethyl cellulose (CMC) were added to deionized water in a mass ratio of 5:2, stirred into a uniform slurry, and the slurry was coated on the negative electrode current collector copper foil, dried, and cut to obtain a negative electrode sheet without a negative electrode structure.

[0171] 4) Isolation film

[0172] Polypropylene film is used as the isolation film.

[0173] 5) Preparation of full battery

[0174] For a gel electrolyte composition and a liquid electrolyte with a viscosity of less than 1000 mPa·s, the positive electrode sheet, separator, and current collector are stacked in order, with the separator positioned between the positive and negative current collectors to provide isolation. The cells are then wound to obtain a bare cell. The tabs are welded to the bare cell, which is then placed in an aluminum case and baked at 80°C to remove water. The electrolyte is then injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium metal battery product of Example 1.

[0175] For gel electrolyte compositions and all-solid electrolytes with a viscosity greater than 1000 mPa·s, the electrolyte is cast onto both sides of the separator. The positive electrode sheet, the separator coated with the electrolyte, and the negative electrode sheet are then stacked in order, with the separator coated with the electrolyte positioned between the positive and negative electrode sheets to provide isolation. The cells are then wound to obtain a bare cell. The tabs are welded to the bare cell, which is then encased in an aluminum shell and baked at 80°C to remove water, yielding an uncharged battery. The uncharged battery then undergoes a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium battery product of Example 1.

[0176] 6) Preparation of button batteries

[0177] For gel electrolyte compositions and liquid electrolytes with a viscosity of less than 1000 mPa·s, the negative electrode current collector, separator, and sodium sheet are stacked in sequence, with the separator placed between the negative electrode current collector and the sodium sheet to act as an insulator. The electrolyte is then injected and assembled into a button battery.

[0178] For gel electrolyte compositions with a viscosity greater than 1000 mPa·s and all-solid-state electrolytes, the negative electrode current collector, the separator coated on both sides of the electrolyte, and the sodium sheet are stacked in sequence, so that the separator and the electrolyte are placed between the negative electrode current collector and the sodium sheet to act as an isolation. The battery is then sealed and assembled into a button cell.

[0179] Examples 2 to 4

[0180] The preparation methods of the batteries of Examples 2 to 4 are similar to those of the battery of Example 1, but the mass contents of the sodium salt, polymer, and solvent are adjusted. The specific parameters are shown in Table 1.

[0181] Example 5

[0182] The battery of Example 5 is prepared in a similar manner to the battery of Example 1, except that the preparation method of the gel electrolyte composition is adjusted. The preparation method is as follows:

[0183] In a dry argon atmosphere, polyethylene oxide (PEO, weight-average molecular weight of 600,000), sodium bis(fluorosulfonyl)imide (NaFSI) and solvent ethylene glycol dimethyl ether (DME) were mixed at a mass ratio of 1:6:3 at 60°C, stirred evenly to completely dissolve NaFSI, and then cooled to room temperature to obtain a supersaturated gel electrolyte composition.

[0184] Examples 6 to 9

[0185] The preparation methods of the batteries of Examples 6 to 9 are similar to those of the battery of Example 5, but the mass contents of the sodium salt, polymer, and solvent are adjusted. The specific parameters are shown in Table 1.

[0186] Examples 10 to 14

[0187] The preparation methods of the batteries of Examples 10 to 14 are similar to those of the battery of Example 1, but the types of sodium salts are adjusted. The specific parameters are shown in Table 1.

[0188] Examples 15 to 17

[0189] The batteries of Examples 15 to 17 were prepared in a similar manner to that of Example 1, except that the type of solvent was adjusted. The specific parameters are shown in Table 1.

[0190] Examples 18 to 22

[0191] The batteries of Examples 18 to 22 were prepared in a similar manner to that of Example 1, except that the type of polymer was adjusted. The specific parameters are shown in Table 1.

[0192] Example 23

[0193] The battery of Example 23 is prepared in a similar manner to that of Example 1, except that the preparation method of the gel electrolyte composition is adjusted. The preparation method is as follows:

[0194] In a dry argon atmosphere, polyethylene oxide (PEO, weight-average molecular weight of 600,000), polyethylene glycol (PEG, weight-average molecular weight of 10,000), sodium bis(fluorosulfonyl)imide (NaFSI) and solvent ethylene glycol dimethyl ether (DME) were mixed in a mass ratio of 1:1:2:6 and stirred evenly to completely dissolve NaFSI to obtain a gel electrolyte composition.

[0195] Examples 24 to 26

[0196] The preparation methods of the batteries of Examples 24 to 26 are similar to those of the battery of Example 5, but the type and mass content of the sodium salt are adjusted. The specific parameters are shown in Table 1.

[0197] Examples 27-28

[0198] The batteries of Examples 27 to 28 were prepared in a similar manner to that of Example 5, except that the type and mass content of the polymer were adjusted. The specific parameters are shown in Table 1.

[0199] Examples 29-30

[0200] The batteries of Examples 29 to 30 were prepared in a similar manner to that of Example 5, except that the types of positive electrode active materials were adjusted. The specific parameters are shown in Table 1.

[0201] Examples 31-32

[0202] The batteries of Examples 31 to 32 were prepared in a similar manner to that of Example 1, except that the types of positive electrode active materials were adjusted. The specific parameters are shown in Table 1.

[0203] Comparative Example 1

[0204] The battery of Comparative Example 1 was prepared in a similar manner to the battery of Example 1, but without adding polymer, to prepare a liquid electrolyte. The specific parameters are shown in Table 1.

[0205] Comparative Example 2

[0206] The preparation method of the battery of Comparative Example 2 is similar to that of the battery of Comparative Example 1, but the type of solvent is adjusted. The specific parameters are shown in Table 1.

[0207] Comparative Example 3

[0208] The preparation method of the battery of Comparative Example 3 is similar to that of the battery of Comparative Example 1, but the type of sodium salt is adjusted. The specific parameters are shown in Table 1.

[0209] Comparative Examples 4-5

[0210] The preparation methods of the batteries of Comparative Examples 4 to 5 are similar to those of the battery of Comparative Example 1, but the mass content of the sodium salt is adjusted. The specific parameters are shown in Table 1.

[0211] Comparative Example 6

[0212] The preparation method of the battery of Comparative Example 6 is similar to that of the battery of Example 1, but the gel electrolyte composition is dried to completely remove the solvent to prepare an all-solid electrolyte composition. The specific parameters are shown in Table 1.

[0213] Comparative Example 7

[0214] The preparation method of the battery of Comparative Example 7 is similar to that of the battery of Example 6, but the mass content of the sodium salt is adjusted. The specific parameters are shown in Table 1.

[0215] 2. Performance Testing

[0216] 1. Gel electrolyte composition performance test

[0217] 1) Viscosity test at different temperatures

[0218] The prepared gel electrolyte composition was allowed to stand for 10 minutes, and the viscosity was first measured using a Brookfield Dveslvtjo rotary viscometer. The test conditions were: 25°C, 40°C, 60°C, or 80°C, a rotation speed of 12 rpm, a 64-piston for viscosities not less than 2000 mPa·s, and a 62-piston for viscosities less than 2000 mPa·s. Three replicate measurements were performed, and the average value was calculated.

[0219] 2) Free solvent content test

[0220] The infrared spectrum of the gel electrolyte composition was measured using a Nicolet iS5 Fourier transform infrared spectrometer. After normalizing the spectrum, the intensity of the solvent characteristic peak was recorded as I1. The infrared spectrum of the solvent of the gel electrolyte composition was measured using the solvent as a reference sample. After normalizing the spectrum, the intensity of the corresponding characteristic peak of the solvent was recorded as I2. I1 / I2 was used as the ratio of the amount of free solvent in the gel electrolyte composition to the amount of solvent. The solvent characteristic peak was selected according to the type of solvent. For ether solvents, the characteristic peak of CO is located at 800-900 cm -1 For ester solvents, the characteristic peak of C=O is located between 850-950cm -1 Between 1700-1800cm -1 When comparing peak intensities, the peak intensity of 850-950 cm -1 The peaks between were compared.

[0221] 3) Measurement of the median particle size of the electrolyte salt crystallized from the supersaturated gel electrolyte composition

[0222] Testing was performed using the centrifugal sedimentation method and a laser particle size analyzer. First, the sample was centrifuged, sedimented, and filtered to obtain crystallized electrolyte salt. Then, 0.1g to 0.13g of the crystallized electrolyte salt sample to be tested was weighed into a 50mL beaker, 5g of acetone was added, and a stir bar approximately 2.5mm in diameter was placed in the beaker, which was then sealed with plastic wrap. After ultrasonic treatment for 5 minutes, the sample was transferred to a magnetic stirrer and stirred at 500 rpm for at least 20 minutes. Two samples were tested from each batch. Testing was performed using a Mastersizer 2000E laser particle size analyzer from Malvern Instruments Ltd., UK.

[0223] 2. Battery performance test

[0224] 1) Ionic conductivity test at different temperatures

[0225] The ionic conductivity testing process for gel electrolyte compositions with a viscosity greater than 1000 mPa·s and all-solid-state electrolytes is as follows: The ohmic impedance of button cells (the positive and negative electrodes are platinum or titanium plates of equal area) is measured using a 1470 multi-channel electrochemical workstation from Solartron, UK. The test temperature is 25°C, 40°C, 60°C, or 80°C, the frequency range is 1 Hz-1 MHz, the perturbation signal is 5 mV, and the ionic conductivity = (electrolyte thickness + separator thickness) / (electrolyte area × electrolyte ohmic impedance). The testing process for the comparative example and other embodiments is the same as above.

[0226] The ionic conductivity test process for gel electrolyte compositions and liquid electrolytes with a viscosity of less than 1000 mPa·s is as follows: the ohmic impedance of a button cell (the electrodes on the positive and negative sides are platinum or titanium sheets of equal area) is measured using a 1470 multi-channel electrochemical workstation from Solartron, a UK company, wherein at least three layers of diaphragms are placed. The test temperature is 25°C, 40°C, 60°C, or 80°C, the frequency range is 1 Hz-1 MHz, the perturbation signal is 5 mV, and the ionic conductivity = total thickness of the multilayer diaphragm / (electrolyte area × electrolyte ohmic impedance).

[0227] 2) Coulombic efficiency test at different temperatures

[0228] The coulomb test process is as follows: at 25°C, 40°C, 60°C or 80°C, the prepared full battery is subjected to a single coulomb efficiency = discharge capacity (Cd1) / charge capacity (Cc1) × 100%, which is one cycle. The charge and discharge cycles are repeated, and the number of cycles n is the number of cycles in which the capacity retention rate reaches 80%. The average coulomb efficiency from the second to the nth cycle is calculated as the coulomb efficiency of the full battery. This coulomb efficiency can represent the stability of battery performance during the cycle. The test process of the comparative example and other embodiments is the same as above.

[0229] 3) Cycle test to maintain 80% of room temperature / high temperature capacity

[0230] The room temperature / high cycle capacity retention test process is as follows: at 25 / 60°C and normal pressure (0.1MPa), the prepared full battery is charged at a constant current of 1C to a voltage of 4V (layered oxide positive electrode) or 3.7V (sodium iron pyrophosphate positive electrode), then charged at a constant voltage of 4 / 3.7V to a current of 0.01C, and then discharged at a constant current of 1C to a voltage of 3.0V. This is one charge and discharge cycle. The capacity of the first discharge is 100%, and the charge and discharge cycle is repeated. When the discharge capacity decays to 80%, the test is stopped and the number of cycles is recorded. The number of cycles when the capacity retention rate reaches 80% is used as an indicator to evaluate the cycle performance of the full battery. The test process of the comparative example and other embodiments is the same as above.

[0231] 4) Room temperature / high temperature storage performance

[0232] After the prepared full battery was allowed to stand for 30 minutes at 25 / 60°C, it was charged to 4V at a constant current rate of 0.1C, then charged to 0.01C at a constant voltage rate of 4V and allowed to stand for 5 minutes. The thickness of the full battery was measured. After storage at 25 / 60°C for 60 days, the thickness of the full battery was measured, and the battery thickness expansion rate was calculated using the following formula: full battery thickness expansion rate = [(thickness after storage - thickness before storage) / thickness before storage] × 100%. The test procedures for the comparative example and other examples are the same as above.

[0233] 3. Analysis of test results of various embodiments and comparative examples

[0234] Batteries of various embodiments and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1, 2, and 3 below.

[0235] Table 1

[0236]

[0237]

[0238] Table 2

[0239]

[0240]

[0241] Table 3

[0242]

[0243]

[0244] According to the above results, the viscosity of the gel electrolyte composition of Examples 1 to 32 at 25°C is 500mPa·s to 100,000mPa·s, wherein the sodium salt in the gel electrolyte composition is selected from sodium chloride, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl)imide or sodium bis(trifluoromethylsulfonyl)imide, the solvent in the gel electrolyte composition is selected from ethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane or ethylene carbonate, and the polymer in the gel electrolyte composition is selected from one or two of polyethylene oxide, poly(vinylidene fluoride-co-hexafluoropropylene), polyethylene glycol, polyvinyl pyrrolidone, and perfluoropolyether. From the comparison of Examples 1 to 4, 10 to 23, and 31 to 32 with Comparative Examples 1 to 3, and Examples 5 to 9, 24 to 30 with Comparative Examples 4 to 5, it can be seen that compared with liquid electrolytes, the gel electrolyte composition has a more suitable viscosity range, which is beneficial to improving the coulombic efficiency of the battery at 60°C. From the comparison of Examples 1 to 32 and Comparative Examples 6 to 7, it can be seen that compared with the all-solid electrolyte, the gel electrolyte composition has a more suitable viscosity range, which is beneficial to improving its ionic conductivity at 25°C, 40°C, 60°C and 80°C.

[0245] From the comparison between Examples 1 to 32 and Comparative Examples 6 to 7, it can be seen that the amount of free solvent in the gel electrolyte composition is 0 to 70% based on the total amount of solvent. Compared with all-solid-state electrolytes, the gel electrolyte composition has a suitable free solvent mass content range, which is conducive to the free movement of ions, thereby improving its ionic conductivity at 25°C, 40°C, 60°C and 80°C.

[0246] Comparisons of Examples 1 to 4 with Comparative Examples 1 to 3, and Examples 5 to 9 with Comparative Examples 4 to 5, show that, based on the total mass of the gel electrolyte composition, the mass content of the sodium salt is controlled to be 5% to 70%. Compared to liquid electrolytes, the gel electrolyte composition can effectively improve the coulombic efficiency of the battery at 25°C, 40°C, and 60°C, thereby broadening the temperature operating range of the battery. Comparisons of Examples 1 to 9 with Comparative Examples 6 to 7 show that, based on the total mass of the gel electrolyte composition, the mass content of the sodium salt is controlled to be 5% to 70%. Compared to all-solid-state electrolytes, the gel electrolyte composition can effectively improve the ionic conductivity at 25°C, 40°C, 60°C, and 80°C, and increase the number of cycles during which the battery's capacity retention rate at 25°C reaches 80%, thereby improving battery performance.

[0247] Comparisons of Examples 1-4 with Comparative Examples 1-3, and Examples 5-9 with Comparative Examples 4-5, show that, by controlling the mass content of the solvent to 20% to 75% based on the total mass of the gel electrolyte composition, the gel electrolyte composition can effectively improve the coulombic efficiency of the battery at 25°C, 40°C, and 60°C, compared to liquid electrolytes, thereby broadening the battery's operating temperature range. Comparisons of Examples 1-9 with Comparative Examples 6-7 show that, by controlling the mass content of the solvent to 20% to 75% based on the total mass of the gel electrolyte composition, the gel electrolyte composition can effectively improve its ionic conductivity and increase the number of cycles during which the battery's capacity retention at 25°C reaches 80%, compared to all-solid-state electrolytes, thereby enhancing battery performance.

[0248] Comparisons of Examples 1-4 with Comparative Examples 1-3, and Examples 5-9 with Comparative Examples 4-5, show that, by controlling the polymer content to be 2% to 20% by mass based on the total mass of the gel electrolyte composition, the gel electrolyte composition can effectively improve the coulombic efficiency of the battery at 25°C, 40°C, and 60°C, compared to liquid electrolytes, thereby broadening the battery's operating temperature range. Comparisons of Examples 1-9 with Comparative Examples 6-7 show that, by controlling the polymer content to be 2% to 20% by mass based on the total mass of the gel electrolyte composition, the gel electrolyte composition can effectively improve its ionic conductivity, increase the number of cycles during which the battery's capacity retention at 25°C reaches 80%, and enhance battery performance, compared to all-solid-state electrolytes.

[0249] Examples 5 to 9 and 24 to 30 are supersaturated gel electrolyte compositions. The viscosity of the supersaturated gel electrolyte composition at 25° C. is 3000 mPa·s to 100,000 mPa·s, optionally 3000 mPa·s to 11,000 mPa·s, and the viscosity at 60° C. is 500 mPa·s to 5000 mPa·s, optionally 500 mPa·s to 3000 mPa·s. The sodium salt in the supersaturated gel electrolyte composition is selected from sodium chloride, sodium hexafluorophosphate, sodium trifluoromethanesulfonate, or sodium bis(fluorosulfonyl)imide; the solvent in the supersaturated gel electrolyte composition is selected from ethylene glycol dimethyl ether or ethylene carbonate; and the polymer in the supersaturated gel electrolyte composition is selected from one or two of polyethylene oxide, polyethylene glycol, or polyvinyl pyrrolidone. Comparison of Examples 5-9 and 24-30 with Comparative Examples 4-5 shows that, compared to liquid electrolytes, supersaturated gel electrolyte compositions having an appropriate viscosity range are beneficial for improving the coulombic efficiency of the battery at 60°C. Comparison of Examples 5-9 and 24-30 with Comparative Examples 6-7 shows that, compared to all-solid-state electrolytes, supersaturated gel electrolyte compositions having an appropriate viscosity range have a more suitable viscosity range, which is beneficial for improving their ionic conductivity at 25°C, 40°C, 60°C, and 80°C.

[0250] From the comparison of Examples 5 to 9 with Examples 1 to 4, Example 24 with Example 10, Example 25 with Example 12, Example 26 to Example 13, Example 27 to Example 20, Example 28 to Example 21, Example 29 to Example 31, and Example 30 to Example 32, it can be seen that compared with other gel electrolyte compositions, the supersaturated gel electrolyte composition has a higher sodium salt concentration, including dissolved sodium salt and precipitated crystallized sodium salt, which is beneficial to improving the coulombic efficiency of the battery at 60°C and 80°C, increasing the number of cycles at which the capacity retention rate reaches 80% at 60°C, and reducing the thickness expansion rate of the battery at 60°C, thereby improving the high temperature performance of the battery.

[0251] Comparisons of Examples 5-9 with Examples 1-4, Example 24 with Example 10, Example 25 with Example 12, Examples 26-13, Examples 27-20, Examples 28-21, Examples 29-31, and Examples 30-32 show that, compared to other gel electrolyte compositions, the supersaturated gel electrolyte composition has a median particle size of sodium salt precipitated and crystallized to be less than or equal to 100 μm, which is beneficial for improving the coulombic efficiency of the battery at 60°C and 80°C, increasing the number of cycles required to achieve 80% capacity retention at 60°C, and reducing the thickness expansion rate of the battery at 60°C, thereby improving the high-temperature performance of the battery. Comparisons of Examples 5-9 and 24-30 with Comparative Examples 4-5 show that, compared to liquid electrolytes, controlling the mass content of sodium salt to 30%-70%, the mass content of solvent to 20%-50%, and the mass content of polymer to 2%-20%, based on the total mass of the supersaturated gel electrolyte composition, is beneficial for improving the coulombic efficiency of the battery at 60°C. From the comparison of Examples 5 to 9, 24 to 30 and Comparative Examples 6 to 7, it can be seen that compared with the all-solid-state electrolyte, controlling the mass content of the sodium salt to 30% to 70%, the mass content of the solvent to 20% to 50%, and the mass content of the polymer to 5% to 20%, based on the total mass of the supersaturated gel electrolyte composition, is beneficial to improving the ionic conductivity of the supersaturated gel electrolyte at 25°C, 40°C, 60°C and 80°C.

[0252] From the comparison of Examples 1 to 4, Examples 10 to 14 with Comparative Examples 1 to 3, and Examples 5 to 9, Examples 24 to 26 with Comparative Examples 4 to 5, it can be seen that the sodium salt in the gel electrolyte composition is selected from sodium chloride, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, or sodium bis(trifluoromethylsulfonyl)imide, which is beneficial for improving the coulombic efficiency of the battery at 60°C and 80°C and improving the battery performance. From Examples 1, 12 to 14 and Examples 10 to 11, compared with the sodium salt selected from sodium chloride or sodium tetrafluoroborate, the sodium salt selected from sodium hexafluorophosphate, sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, or sodium bis(trifluoromethylsulfonyl)imide can further improve the coulombic efficiency of the battery at 60°C and increase the number of cycles at which the battery capacity retention rate at 25°C and 60°C reaches 80%, significantly improving the battery performance.

[0253] Comparisons of Examples 1 to 4, Examples 15 to 17 with Comparative Examples 1 to 3, and Examples 5 to 9 with Comparative Examples 4 to 5 show that the solvent in the gel electrolyte composition is selected from ethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, or ethylene carbonate, which is beneficial for improving the coulombic efficiency of the battery at 60°C. Compared with the solvent selected from ethylene carbonate, Examples 1, 15 to 16 and Example 17 show that the solvent selected from ethylene glycol dimethyl ether, tetrahydrofuran, or 1,3-dioxolane can further improve the coulombic efficiency of the battery at 25°C, 40°C, 60°C, and 80°C, increase the number of cycles during which the battery capacity retention reaches 80% at 25°C and 60°C, and reduce the thickness expansion rate of the battery at 25°C and 60°C, thereby significantly improving the battery performance and safety.

[0254] Comparisons of Examples 1-4, Examples 18-23 with Comparative Examples 1-3, and Examples 5-9, Examples 27-28 with Comparative Examples 4-5 show that the polymer in the gel electrolyte composition is selected from one or two of polyethylene oxide, poly(vinylidene fluoride-co-hexafluoropropylene), polyethylene glycol, polyvinyl pyrrolidone, and perfluoropolyether, which is beneficial for improving the coulombic efficiency of the battery at 25°C and 60°C, and the number of cycles during which the battery capacity retention reaches 80% at 60°C. Compared to the polymer selected from polyvinyl pyrrolidone, the polymer selected from one or two of polyethylene oxide, poly(vinylidene fluoride-co-hexafluoropropylene), polyethylene glycol, and perfluoropolyether can further reduce the thickness expansion rate of the battery at 25°C, significantly improving the battery safety.

[0255] From the comparison of Examples 1, 12 to 16, 18 to 20, 22 to 23 with Examples 10 to 11, 17 and 21, it can be seen that the sodium salt in the gel electrolyte composition is selected from sodium hexafluoroborate, sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl)imide or sodium bis(trifluoromethylsulfonyl)imide, the solvent is selected from ethylene glycol dimethyl ether, tetrahydrofuran or 1,3-dioxolane, and the polymer is selected from one or two of polyethylene oxide, polyethylene glycol, perfluoropolyether and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer, which can achieve both electrical performance and safety of the battery.

[0256] From the comparison between Example 1 and Examples 31-32, it can be seen that compared with the use of Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2 or ZrO2, TiO2 coated Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9 Mg 1 / 18Using O2 as the positive electrode active material and Na4Fe3(PO4)2P2O7 as the positive electrode active material is more conducive to improving the coulombic efficiency of the battery at 25°C, 40°C, 60°C and 80°C, increasing the battery's capacity retention rate to 80% at 25°C and 60°C, and reducing the battery's thickness expansion rate at 25°C, thereby greatly improving the battery's performance and safety.

[0257] From the comparison between Example 30 and Example 29, and Example 32 and Example 31, it can be seen that compared with the use of Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2 is used as the positive electrode active material, and ZrO2 and TiO2 coated Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9 Mg 1 / 18 O2 as the positive electrode active material is more conducive to improving the coulombic efficiency of the battery at 25°C, 40°C, 60°C and 80°C, increasing the number of cycles of the battery's capacity retention rate at 25°C to 80%, and reducing the thickness expansion rate of the battery at 25°C and 60°C, thereby greatly improving the performance and safety of the battery.

[0258] From the comparison between Example 29 and Example 31, and Example 30 and Example 32, it can be seen that compared with the unsaturated gel electrolyte composition, the supersaturated gel electrolyte composition is more conducive to improving the coulombic efficiency of the battery at 25°C, 40°C, 60°C and 80°C, increasing the number of cycles of the battery capacity retention rate at 25°C and 60°C to 80%, and reducing the thickness expansion rate of the battery at 25°C and 60°C, thereby greatly improving the performance and safety of the battery.

[0259] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A gel electrolyte composition, characterized in that: The viscosity of the gel electrolyte composition at 25° C. is 500 mPa·s to 100,000 mPa·s.

2. The gel electrolyte composition according to claim 1, characterized in that The gel electrolyte composition comprises a solvent, wherein, based on the total amount of the solvent, the ratio of the amount of the free solvent in the gel electrolyte composition to the total amount of the solvent is n FS 0% <n FS ≤70%.

3. The gel electrolyte composition according to claim 1 or 2, characterized in that: The mass content of the solvent is 20% to 75% based on the total mass of the gel electrolyte composition.

4. The gel electrolyte composition according to any one of claims 1 to 3, characterized in that The gel electrolyte composition further includes an electrolyte salt, and the mass content of the electrolyte salt is 5% to 70% based on the total mass of the gel electrolyte composition.

5. The gel electrolyte composition according to any one of claims 1 to 4, characterized in that The gel electrolyte composition further comprises a polymer, and the mass content of the polymer is 2% to 20% based on the total mass of the gel electrolyte composition.

6. The gel electrolyte composition according to any one of claims 1 to 5, characterized in that The gel electrolyte composition is a supersaturated gel electrolyte composition at 25°C.

7. The gel electrolyte composition according to claim 6, characterized in that: The supersaturated gel electrolyte composition has a viscosity of 3000 mPa·s to 100000 mPa·s at 25° C., and a viscosity of 500 mPa·s to 5000 mPa·s at 60° C.

8. The gel electrolyte composition according to claim 6 or 7, characterized in that: The supersaturated gel electrolyte composition has a viscosity of 3000 mPa·s to 11000 mPa·s at 25° C., and a viscosity of 500 mPa·s to 3000 mPa·s at 60° C.

9. The gel electrolyte composition according to any one of claims 6 to 8, characterized in that The supersaturated gel electrolyte composition includes a dissolved electrolyte salt and a precipitated crystal electrolyte salt.

10. The gel electrolyte composition according to claim 9, characterized in that The median particle size of the precipitated crystals of the electrolyte salt is 100 μm or less.

11. The gel electrolyte composition according to any one of claims 6 to 10, characterized in that Based on the total mass of the supersaturated gel electrolyte composition, the mass content of the electrolyte salt is 30% to 70%, the mass content of the solvent is 20% to 60%, and the mass content of the polymer is 2% to 20%.

12. The gel electrolyte composition according to any one of claims 4 to 11, characterized in that The electrolyte salt comprises a sodium salt, and the sodium salt comprises one or more of sodium chloride, sodium bromide, sodium nitrate, sodium perchlorate, sodium hexafluorophosphate, sodium tetrafluoroborate, sodium tetrafluoroyttrium, sodium hexafluoroarsenate, sodium tetraphenylborate, sodium acetate, sodium trifluoroacetate, sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethylsulfonyl)imide, and sodium (perfluorobutylsulfonyl)imide, and optionally comprises one or more of sodium hexafluorophosphate, sodium trifluoromethylsulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide.

13. The gel electrolyte composition according to any one of claims 2 to 12, characterized in that: The solvent comprises one or more of an ether organic solvent, an ester organic solvent, and a sulfur-containing organic solvent. The solvent comprises one or more of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, 1,3-dioxolane, ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, fluoroethylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, γ-butyrolactone, 1,3-propane sultone, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, propyl propionate, ethyl butyrate, and dimethyl sulfoxide, and optionally comprises one or more of ethylene glycol dimethyl ether, tetrahydrofuran, and 1,3-dioxolane.

14. The gel electrolyte composition according to any one of claims 5 to 13, characterized in that The polymer comprises one or more of polyethylene oxide, polyethylene glycol, polyvinyl pyrrolidone, polymethyl methacrylate, polyvinylidene fluoride, polyvinyl alcohol, polyacrylonitrile, polyvinyl chloride, polyacrylamide, polytrimethylene carbonate, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer, and optionally comprises one or more of polyethylene oxide, polyethylene glycol, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer.

15. The gel electrolyte composition according to any one of claims 5 to 14, characterized in that The electrolyte salt comprises one or more of sodium trifluoromethanesulfonate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluoromethylsulfonyl)imide; the solvent comprises one or more of ethylene glycol dimethyl ether, tetrahydrofuran, and 1,3-dioxolane; and the polymer comprises one or more of polyethylene oxide, polyethylene glycol, perfluoropolyether, and poly(vinylidene fluoride-co-hexafluoropropylene) copolymer.

16. A secondary battery, characterized in that: The invention comprises a positive electrode sheet and the gel electrolyte composition according to any one of claims 1 to 15.

17. The secondary battery according to claim 16, characterized in that: The secondary battery includes at least one of a lithium battery and a sodium battery.

18. The secondary battery according to claim 16 or 17, characterized in that: The secondary battery is a negative electrode-free sodium battery.

19. The secondary battery according to any one of claims 16 to 18, characterized in that: The positive electrode sheet includes a positive electrode active material, wherein the positive electrode active material includes at least one of a transition metal layered oxide, a polyanion compound and a Prussian blue compound, including NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2、Na(Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 )O2、Na 2 / 3 Ni 1 / 6 Mn 2 / 3 Cu 1 / 9 Mg 1 / 18 O2, Na4Fe3(PO4)2P2O7, NaFePO4, Na3V2(PO4)3, Na 1.9 One or more of CoFe(CN)6, Na2NiFe(CN)6, NaMnFe(CN)6.

20. The secondary battery according to any one of claims 16 to 19, characterized in that: The surface of the positive electrode active material has a coating layer, and the coating layer includes one or more of carbon material, ZrO2, TiO2, polyaniline, polypyrrole, poly(3,4-ethylenedioxythiophene), aluminum oxide, zinc oxide, titanium oxide, zirconium oxide, magnesium oxide, silicon oxide, lanthanum oxide, sodium fluoride, lithium fluoride and aluminum fluoride, and the carbon material includes one or more of amorphous carbon, graphite and graphene.

21. A battery module, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 16 to 20.

22. A battery pack, characterized in that: The invention comprises the secondary battery according to any one of claims 16 to 20 or the battery module according to claim 21.

23. An electrical device, characterized in that: The invention comprises at least one of the secondary battery according to any one of claims 16 to 20, the battery module according to claim 21, or the battery pack according to claim 22.